Aesthetic judgements and motivation. Issue 6 (18th August 2017) - Archer, Alfred
Abstract: Are aesthetic judgements cognitive, belief-like states or non-cognitive, desire-like states? There have been a number of attempts in recent years to evaluate the plausibility of a non-cognitivist theory of aesthetic judgements. These attempts borrow heavily from non-cognitivism in metaethics. One argument that is used to support metaethical non-cognitivism is the argument from Motivational Judgement Internalism. It is claimed that accepting this view, together with a plausible theory of motivation, pushes us towards accepting non-cognitivism. A tempting option, then, for those wishing to defend aesthetic non-cognitivism, would be to appeal to a similar argument. However, both Caj Strandberg and Walter Sinnott-Armstong have argued that Internalism is a less plausible claim to make about aesthetic judgements than about moral judgements by raising objections against aesthetic internalism. In this paper, I will argue that both of these objections can be raised against internalism about moral judgements as well. As a result, internalism is no less plausible a claim to make about aesthetic judgements than about moral judgements. I will then show how a theory of internalism about normative judgements in general is capable of avoiding both of these objections.